Characterizing nutrient status and growth of Macaranga gigantea in tropical rainforest gaps after selective logging in East Kalimantan, Indonesia - DWI SUSANTO; HAYATUDIN HAYATUDIN; ARIS SETIAWAN; HERI PURNOMO; DADDY RUHIYAT; RUDIANTO AMIRTA (Society for Indonesian Biodiversity, 2017)
Susanto D, Hayatudin, Setiawan A, Purnomo H, Ruhiyat D, Amirta R. 2017. Characterizing nutrient status and growth of Macaranga gigantea in tropical rainforest gaps after selective logging in East Kalimantan, Indonesia. Biodiversitas 18: 996-1003. Selective logging caused the formation of forest gaps, which stimulate the growth of the pioneer tree species. This study aims to determine the characteristic of soil nutrients status and plant growth of Macaranga gigantea in the tropical rainforest gaps after selective logging in East Kalimantan, Indonesia. We established research plots 50mx50m in natural forest production, 1 until 10 years after selective logging. The measured data of each plot is the number of trees of M. gigantea, its stem diameter, and its height, and also the soil and leaf nutrient concentration. The results showed that the soil has a pH (H2O) of 5.3 ± 0.27, cation exchange capacity of 10.6 ± 2.98 meq. 100 g-1, base saturation of 27.7 ± 10.44%, while the concentration of nutrients carbon of 1. 04 ± 0.27%, nitrogen of 0.10± 0.02%, phosphorus of 6.35 ± 3.4%, potassium of 67.15± 30.1%, calcium of 1.7 ± 1.09% and magnesium of 0. 99 ± 0.8%. The highest stem diameter and height of M. gigantea (19.5 cm; 18.07 m) was obtained in plots of 8 years after selective logging and then declined, while the highest diameter increment and height increment obtained in plants located in a plot of 4 years after selective logging and decline until 10 years after selective logging. The concentration of nutrients accumulated in the leaves of M. gigantea was N with 1.51 ± 0.19%, P with 0.16 ± 0.01%, K with 1.37 ±0.28%, Ca with 1.78 ± 0, 43% and Mg with 1.53 ± 0.37%. The soil nutrients concentration of N, K, Ca and Mg correlated with plant growth of M. gigantea (p? 0.05), potassium concentration of soil positively correlated with a potassium concentration of leaves (p? 0.05), whereas magnesium concentration in the leaf correlated with plant growth (p? 0.05). We suspect that bases nutrient elements, potassium, calcium, and magnesium are nutrients absorbed in large quantities by M. gigantea and extremely important to its growth.